Energy management system for AC/DC HMGS integrated with interconnected renewable sources and interlinking converter - Syed Abdul Razzaq; Vairavasamy Jayasankar (International Journal of Applied Power Engineering (IJAPE), 2023)
AC/DC hybrid micro grid system (HMGS) is designed with renewable energy sources (RES) and battery energy storage system (BESS) with unique control schemes, interfaced with multi terminal interlinking converters (ILCs). This ILC operates on droop control scheme to guarantee bidirectional power sharing to AC/DC sub grids. The power sources in AC/DC sub grids like PV, Fuel cell, BESS are controlled by advance control methods for maximum power extraction with power quality. A three-level control structure is designed for optimal energy management system (EMS). The first level confirms the power balance in AC/DC sub grid with autonomous bidirectional power transfer via ILC in islanded mode. The second level tracks the batteries state of charge (SoC), based on the minimum and maximum SoC the battery operates for charging and discharging. The third level gives the power redundant capability for critical loads connected in AC/DC sub grid for DC system and single-phase system.